224k views
2 votes
Select "ALL" that are right

Select "ALL" that are right-example-1
User Lynks
by
5.3k points

1 Answer

5 votes

Answer:

These steps can be used:

  • combine -6 and 4
  • combine 15 and -3
  • multiply 2 by x and -2

Explanation:

The equation could be solved as follows:

2(x -6 +4) = 15 -3 given

2(x -2) = 15 -3 combine -6 and 4

2(x -2) = 12 combine 15 and -3

2x -4 = 12 multiply 2 by x and -2

2x = 16 add 4 to both sides

x = 8 divide both sides by 2

_____

Alternate solution

At step 4, you could have

x -2 = 6 divide both sides by 2

x = 8 add 2 to both sides

User Merterpam
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.